El uso de material reciclado como recurso didáctico en el aprendizaje en los niños de 3 a 4 años en el Centro de Educación Inicial Planeta Azul, Cantón Riobamba - Montoya Llanga, Lizbeth Valeria (2024)
The present research work, entitled "The use of recycled material as a teaching resource in learning in children aged 3 to 4 years at Planeta Azul Early Childhood Education Center of the Riobamba canton of the Chimborazo Province", had as its main objective, to determine the benefits generated by the use of recycled material as a teaching resource in learning in children of this age, the level of depth was descriptive with bibliographic documentary characteristic, this allowed the collection of information reflected in the theoretical framework, field since the research was carried out in the same place where the problem was presented and qualitative because it explains the results obtained from the study group. The instrument used was an observation sheet, which consists of 10 indicators with the assessment scale, started, in process and acquired, in the use of recycled materials that resulted in: children actively participate, show interest, identify different types of recycled materials, and use their creativity to find new uses for them. The population studied was 11 students, from which no sample was obtained because it was a small population. Through the analysis of the elements, it was concluded that the proposed strategies for creating educational resources with recycled materials are effective, as they support pedagogical development and foster skills such as creativity, critical thinking, and motor skills, as well as promoting early ecological awareness. This contributes to forming responsible citizens and offers a meaningful and practical learning experience.